Structural optimisation and analysis of internally heat integrated reactive distillation column. (2015) - Bo, Shoushi; Wang, Jian; Sun, Lanyi; Bai, Fei; He, Kang
In this contribution, the model for hydrolysis of methyl acetate (MeAc) occurring in an internally heat integrated reactive distillation column (R-HIDiC) was built by using Aspen Plus software. And several configurations of R-HIDiC were proposed. The effects of the configuration on the energy saving were investigated on the premise of ensuring the purity of products and minimum approach temperature. The results reveal that configuration has significant influence on the performance of R-HIDiC for the hydrolysis reaction of MeAc and the optimal structure is determined. Sensitivity analysis has also been conducted to tune the design and operating variables of R-HIDiC.